Dynamics in the activity of peroxidase and its isoforms in leaves of different apple cultivars - A. E. Mishko; E. O. Lutskiy (Труды по прикладной ботанике, генетике и селекции)
Background. Various approaches are used for identification of the most resistant fruit crop cultivars, including the analysis of different physiological and biochemical indicators. In Krasnodar Territory, Russia, one of the major stressors in summer is the hydrothermal stress. Drought and heat lead to an oxidative stress, as reactive oxygen species are produced in plant cells. Plants respond to oxidative damage by activating antioxidant enzymes, such as superoxide dismutase, catalase, and various peroxidases. Peroxidase is able to decompose hydrogen peroxide. Peroxidase activity was calculated under natural summertime changes in the hydrothermal pattern (control) and in simulated high-temperature conditions.Materials and methods. Three apple cultivars of Russian breeding, ‘Fortuna’, ‘Soyuz’ and ‘Prikubanskoe’, and cv. ‘Ligol’ of Polish origin were studied. In the summers of 2018–2019, their leaf samples were analyzed to assess peroxidase activity and its isozyme composition under control and stress conditions. Native electrophoresis in polyacrylamide gel was used for separation of peroxidase isoforms. Malondialdehyde content was measured to identify oxidative stress levels in apple leaves.Results. The tested indicators demonstrated a high degree of heterogeneity induced by both cultivar specificity and seasonal weather dynamics. Peroxidase isoforms with a molecular weight of 70 to 60 kDa, characterized by the maximum level of variability (1–4 isoforms), were isolated. Two other groups included 1–3 isoforms with a molecular weight of ~130–100 kDa, and one with a molecular weight of ~55 kDa. The highest enzyme activity was found in cvs. ‘Fortuna’ and ‘Soyuz’ in July 2018, the hottest month during the period of research. Under simulated conditions, the triploid cultivar ‘Soyuz’ was least susceptible to the stress impact.